Titanium Plate Fixation versus Conventional Closure for Sternal Dehiscence after Cardiac Surgery - Vos, Roemer J.; Jongbloed, Lisa; Sonker, Uday; Kloppenburg, Geoffrey T. L. (The Thoracic and Cardiovascular Surgeon, 2017)
Background Postoperative sternal dehiscence with or without mediastinitis is a complication of cardiac surgery leading to considerable disability. Titanium plate fixation can provide sternal stability in patients with a dehiscent sternum. The aim of this study is to compare clinical outcomes of titanium plate fixation with conventional treatment methods such as steel wire cerclage and pectoralis muscle reconstruction.Patients and Methods A retrospective analysis was performed on 42 patients who underwent sternal refixation after dehiscence or secondary wound closure after poststernotomy mediastinitis. Clinical outcomes during hospital stay and follow-up were determined.Results Twenty patients were closed using sternal plates. Twenty-two patients were closed conventionally: 8 using pectoral muscle reconstruction and 14 using cerclage steel wires. There were no differences in baseline characteristics between the two groups. Indications of sternal closure were similar. Sternal stability at hospital discharge was achieved more often using sternal plating (90 vs. 50%, p = 0.005), mainly in patients closed after treatment of poststernotomy mediastinitis (100 vs. 22%, p = 0.002). Hospital stay was similar in both groups (10 [5–23] vs. 12 (5–21) days, p = 0.527). There was no inhospital mortality.Conclusion Titanium plate fixation is superior in stabilizing the sternal bone when compared with conventional refixation methods, especially in secondary closure after poststernotomy mediastinitis.
Keywords: wound infection; sternum; wound healing